2014
DOI: 10.1007/s13197-014-1480-x
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of acetylated starches from Indian black gram (Phaseolus mungo L.) cultivars

Abstract: Starches separated from three black gram cultivars were modified by acetylation and compared to their native starches. Acetylation was carried out by treating starches with 0.04 and 0.08 g of acetic anhydride/g of starch dry weight basis (db) at 25 °C. The extent of acetylation increased proportionally with the concentration of acetic anhydride used. Retrogradation of acetylated starch pastes decreased significantly (p ≤ 0.05) as revealed by significant decrease in syneresis, increased freeze thaw stability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
10
12
0
Order By: Relevance
“…The amylose content of different legume starches varied from 30.61% to 33.55%, and the highest amylose content was found in red adzuki starch, whereas the lowest amylose content was found in faba bean starch. These values were similar with the values previously reported for black gram (30.33%-40.64%; Wani, Sogi, & Gill, 2015), but relatively lower than those reported for chickpeas (46.5%) and pinto beans (52.4%; Yañez-Farias, Moreno-Valencia, Falcón-Villa, & Barrón-Hoyos, 1997), and field peas (42.9%-43.7%; Ratnayake, Hoover, Shahidi, Perera, & Jane, 2001). The different amylose content among different starch varieties could be attributed to different enzyme activity that involved in the biosynthesis of starch molecules within the starch granules (Krossmann & Lloyd, 2000), and the soil type and climatic conditions during growth and granule size distribution (Singh, Mc-Carthy, & Singh, 2006 The fissures structure could also be observed on mung bean starch under light microscope (Li, Shu, Zhang, & Shen, 2011).…”
Section: Proximate Composition Of Legume Starchessupporting
confidence: 93%
“…The amylose content of different legume starches varied from 30.61% to 33.55%, and the highest amylose content was found in red adzuki starch, whereas the lowest amylose content was found in faba bean starch. These values were similar with the values previously reported for black gram (30.33%-40.64%; Wani, Sogi, & Gill, 2015), but relatively lower than those reported for chickpeas (46.5%) and pinto beans (52.4%; Yañez-Farias, Moreno-Valencia, Falcón-Villa, & Barrón-Hoyos, 1997), and field peas (42.9%-43.7%; Ratnayake, Hoover, Shahidi, Perera, & Jane, 2001). The different amylose content among different starch varieties could be attributed to different enzyme activity that involved in the biosynthesis of starch molecules within the starch granules (Krossmann & Lloyd, 2000), and the soil type and climatic conditions during growth and granule size distribution (Singh, Mc-Carthy, & Singh, 2006 The fissures structure could also be observed on mung bean starch under light microscope (Li, Shu, Zhang, & Shen, 2011).…”
Section: Proximate Composition Of Legume Starchessupporting
confidence: 93%
“…The F‐AM ranged from 3.06% to 28%, while L‐AM ranged from 2.20% to 13.38%. The results obtained for the T‐AM were similar to values of 30.33%–40.64% reported by Wani, Sogi, and Gill () for starches from black gram. The values obtained in this study were relatively higher than those reported for starches from rice (21.88%–22.64%) by Ashogbon and Akintayo ().…”
Section: Resultssupporting
confidence: 89%
“…In recent years, interest has increased in the utilisation of black gram in different forms rather than traditional way as the whole seeds and decorticated split seeds -dhal (Wani, Sogi, & Gill, 2013b). It is also processed into flour (Wani et al, 2013b), starch (Sathe, Rangnekar, Deshpande, & Salunkhe, 1982;Wani, Sogi, & Gill, 2014) and protein isolates (Shaheen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%